Development Of Professional Competence Of Students Based On Mathematics Training Through Software Tools - Ruzimurodov Ikhtiyor Nishanovich; Nishonov Sardor Ixtiyor o’g’li (Genius Journals, 2023)
In this this article given some recommendations to teach you how to develop a software product using the Python programming language. In addition, interdisciplinary integration has been shown to be important in preparing future mathematicians for professional careers.
Keywords: Use of Python programming code; graphics; integratsion; compilation